Pengaruh Kinerja Keuangan Terhadap Harga Saham - Muhammad Rivandy Putra; Dian Hakip Nurdiansyah (Jurnal Dinamika Ekonomi & Bisnis, 2022)
Before investing, an investor must see what can affect the price of the stock. Therefore, this research intends to see whether there is a contribution among ROA, ROE and DER to the stock prices of the sample companies. Samples were taken from advertising, printing & equipment companies listed on the IDX in 2016-2020. Multiple regression analysis was used to analyze and used hypothesis testing. The test results partially proved that ROA and ROE did not contribute to stock prices, while DER contributed to them.